2021
DOI: 10.1111/jen.12939
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of small heat shock proteins providing evidence of temperature tolerance in Hyphantria cunea

Abstract: A substantial increase in the occurrence of extremely high‐ or low‐temperature events caused by global climate change has imposed pressure on the survival and reproduction of invertebrates. Hyphantria cunea (H. cunea; Lepidoptera: Arctiidae) is a worldwide defoliator and has become a major forestry and agricultural pest during the past three decades in China. The thermal and cold tolerance has directly affected the population and geographical distribution of H. cunea, which remains poorly understood. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…This may be attributed to the fact that the temperature will exceed the regulatory range of sHsps on the body with the time extension, resulting in the stagnation of the gene transcription. 39 Similar results were also found in Hyphantria cunea, where the expression of HCsHsp28.7 showed a fluctuating trend of first increasing and then declining with the time extension after treatment at −10 °C for 1, 2, and 3 h. 40 GpHSP21.4 in Glyphodes pyloalis was downregulated at 4 h following exposure to cold treatment. 41 These results indicated that the response of sHsps to low-temperature stress at the transcription level depends on the severity and duration of the low temperature.…”
Section: Discussionsupporting
confidence: 70%
“…This may be attributed to the fact that the temperature will exceed the regulatory range of sHsps on the body with the time extension, resulting in the stagnation of the gene transcription. 39 Similar results were also found in Hyphantria cunea, where the expression of HCsHsp28.7 showed a fluctuating trend of first increasing and then declining with the time extension after treatment at −10 °C for 1, 2, and 3 h. 40 GpHSP21.4 in Glyphodes pyloalis was downregulated at 4 h following exposure to cold treatment. 41 These results indicated that the response of sHsps to low-temperature stress at the transcription level depends on the severity and duration of the low temperature.…”
Section: Discussionsupporting
confidence: 70%
“…We found that the relative expression levels of HcHSPs, except for HcHSP21.4, were significantly up-regulated under heat stress and continued to increase with the increase in temperature stress. In previous studies, four of the six identified sHSPs were sensitive to high temperatures [35]. These results indicate that H. cunea has strong heat tolerance, which may enhance its survival as it spreads to the warmer southern areas of China.…”
Section: Discussionmentioning
confidence: 55%
“…Our previous investigations revealed that the Ltim50 values for H. cunea 4th-instar larvae were 62.0 h at 40 • C, 14.5 h at 43 • C, and even 2.3 h at 45 • C [35]. To consider the differences in the thermotolerance of H. cunea at different developmental stages, we set the treatment duration to one hour and used 43 • C as the upper temperature limit.…”
Section: Sample Preparationmentioning
confidence: 99%